Molecular Characterization of AmpC Beta-Lactamase Gene Producing Carbapenem-Resistant Klebsiella Pneumoniae from Hilla River Waters-Iraq - Fatima Moeen Abbas (Journal of Global Pharma Technology, 2017)
This study was carried out to identify the prevalence of blaAmpC  producing Klebsiella pneumoniae isolated from surface waters of Hilla River. During the period from January to April 2015,one hundred and one water samples were collected from 10 various locations of Hilla river. Thirty five (34.6%) isolates were specified as K. pneumoniae. All K. pneumoniae isolates were subjected to antibiotic susceptibility testing using Kirby-Bauer disk diffusion method. The higher level of resistance was observed for penicillin antibiotics (ampicillin and piperacillin) with (57.14%) and (54.28%) resistance rate, respectively. Cefoxitin resistant isolates were checked for AmpC β- lactamase production phenotypically using modified three dimensional tests. Four (25%) isolates were screen-positive. Carbapenem resistance was identified in 2 isolates of K. pneumoniae, these were analyzed further by Polymerase Chain Reaction (PCR) assay for detection blaAmpC gene, 2 (100%) isolates gave positive result.Keywords: Klebsiella pneumoniae, AmpC β-lactamase, Carbapenem resistance, PCR, River water.